Patient‐ and xenograft‐derived organoids recapitulate pediatric brain tumor features and patient treatments - Chiara Lago; Aniello Federico; Gloria Leva; Norman L Mack; Benjamin Schwalm; Claudio Ballabio; Matteo Gianesello; Luana Abballe; Isabella Giovannoni; Sofia Reddel; Sabrina Rossi; Nicolas Leone; et al. (EMBO Molecular Medicine)
Abstract Brain tumors are the leading cause of cancer‐related death in children. Experimental in vitro models that faithfully capture the hallmarks and tumor heterogeneity of pediatric brain cancers are limited and hard to establish. We present a protocol that enables efficient generation, expansion, and biobanking of pediatric brain cancer organoids. Utilizing our protocol, we have established patient‐derived organoids (PDOs) from ependymomas, medulloblastomas, low‐grade glial tumors, and patient‐derived xenograft organoids (PDXOs) from medulloblastoma xenografts. PDOs and PDXOs recapitulate histological features, DNA methylation profiles, and intratumor heterogeneity of the tumors from which they were derived. We also showed that PDOs can be xenografted. Most interestingly, when subjected to the same routinely applied therapeutic regimens, PDOs respond similarly to the patients. Taken together, our study highlights the potential of PDOs and PDXOs for research and translational applications for personalized medicine.